IEEE International Conference on Systems Engineering 1989
DOI: 10.1109/icsyse.1989.48728
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of switching schemes in isotropic networks

Abstract: This paper is a comparative study of two switching schemes for isotropic networks, namely, single hop and cut-through communication schemes. The comparison between the two is based on the time delay for a packet to go through a given path, characterized by the number of links between source and destination. Each sclieme is modeled by a discrete Markov chain. The research results show how the performance of the communication schemes depend on the path length, the load on the communication network and the error … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…(8) A systematic review of socioeconomic differences in food habits in Europe indicated that lower socio-economic status has an unhealthier consumption pattern. (9) Educational level and household income significantly impacted eating habits. (10) A study conducted on Saharawi refugees living in Algeria concluded that low socioeconomic status lacks dietary diversity.…”
Section: Introductionmentioning
confidence: 99%
“…(8) A systematic review of socioeconomic differences in food habits in Europe indicated that lower socio-economic status has an unhealthier consumption pattern. (9) Educational level and household income significantly impacted eating habits. (10) A study conducted on Saharawi refugees living in Algeria concluded that low socioeconomic status lacks dietary diversity.…”
Section: Introductionmentioning
confidence: 99%